Postmortem distribution of chlorpyrifos-methyl, fenitrothion, and their metabolites in body fluids and organ tissues of an intoxication case. (November 2017) - Takayasu, Tatsunori; Yamamoto, Hiroki; Ishida, Yuko; Nosaka, Mizuho; Kawaguchi, Mariko; Kuninaka, Yumi; Kimura, Akihiko; Kondo, Toshikazu
Highlights: Simultaneous postmortem distributions of chlorpyrifos-methyl and its metabolite 3, 5, 6-trichloro-2-pyridinol, and fenitrothion and its metabolite 3-methyl-4-nitrophenol in the body fluids and organ tissues are presented. Ratios of chlorpyrifos-methyl and fenitrothion concentrations in body fluids and organ tissues show 3 groups; group 1 (brain, lung, kidney), group 2 (liver and blood), group 3 (urine) during an absorption period. Abstract: We herein report a fatal intoxication case caused by the ingestion of the insecticides chlorpyrifos-methyl (CPFM) and fenitrothion (MEP). A 70-year-old man was found dead in his house and a cup containing a small amount of agricultural chemicals was on the table near his body. External and internal examinations revealed no injuries. In a gas chromatography–mass spectrometry (GC–MS) screening test, CPFM, MEP, and their metabolites, 3, 5, 6-trichloro-2-pyridinol (TCPY) and 3-methyl-4-nitrophenol (3MNP), respectively, were qualitatively detected in his stomach contents. The concentrations (µg/g) of CPFM, TCPY, MEP, and 3MNP in the extracts of each body fluid and organ tissue were assessed by GC–MS and were as follows: 27.8, 56.2, 17.2, and 2.82 (heart blood); 6.60, 42.9, 1.80, and 2.59 (peripheral blood); 0.0821, 45.9, 2, 09, and 102 (urine); 21.4, 26.6, 76.2, and 3.83 (brain (frontal portion)); 16.1, 101, 9.67, and 1.26 (liver); 7.45, 101, 21.4, and 26.1 (right kidney); and 73, 500, 9750, 232, 000, and 1880 (stomach contents), respectively. Based on these results and autopsy findings, the cause of death was acute fatal intoxication by CPFM and MEP.